The Extended Gate – A Modern Solution to Port Hinterland Connectivity - Dorathy, M.Bina Celine (International Journal of Psychosocial Rehabilitation, 2020)
Through its ambitious sagarmala project, the government is investing 91,371 crores to expand port capacity by 884 mt by 2035. The Shipping Ministry has identified six locations to build new ports. Besides this several new ports built with private funds have also become operational adding to the capacity.Under such circumstances the world bank has raised concern over the increasing port capacity in India. The 12 major ports run by the Central governmenthave handled a combined 679.35 mt of cargo in the year upto March 2018, operating at a capacity utilisation of only 50 per cent.Similar concerns have been expressed by DP World and PSA who are operating multiple facilities from India. This paper makes an attempt to provide an overview of the developments happening in hinterland connectivity and proposes the extended gate concept as a means to improve port connectivity